2022
DOI: 10.2147/ijn.s351814
|View full text |Cite
|
Sign up to set email alerts
|

A Composite Deferoxamine/Black Phosphorus Nanosheet/Gelatin Hydrogel Scaffold for Ischemic Tibial Bone Repair

Abstract: Introduction Bone delay union is mostly caused by lack of blood supply. Although autografts, allografts and artificial bone have been widely used to treat bone delay union, the bone regeneration fails in the ischemic site accompanied by the bone donor site complications and disease transmission. Recently, there is a growing recognition of the importance of hydrogel scaffolds which are regarded as an eligible engineer tissue for bone repair. However, hydrogel is still limited in improving neovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 57 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…The process of vascular formation is highly coupled with skeletal reconstruction; hence, the designs of hydrogel materials that are both pro-angiogenic and osteoconductive have a promising application in promoting bone injury repair. Xu et al [ 65 ] prepared a hydrogel by crosslinking BPNS, deferoxamine (DFO), and gel solution using UV radiation. BPNS was employed to facilitate the controlled release of PO 4 3− and DFO, activating critical angiogenic genes such as vascular endothelial growth factor (VEGF), thereby promoting angiogenesis and accelerating the process of bone defect repair.…”
Section: Bp-based Composite Biomaterials For Tissue Repairmentioning
confidence: 99%
“…The process of vascular formation is highly coupled with skeletal reconstruction; hence, the designs of hydrogel materials that are both pro-angiogenic and osteoconductive have a promising application in promoting bone injury repair. Xu et al [ 65 ] prepared a hydrogel by crosslinking BPNS, deferoxamine (DFO), and gel solution using UV radiation. BPNS was employed to facilitate the controlled release of PO 4 3− and DFO, activating critical angiogenic genes such as vascular endothelial growth factor (VEGF), thereby promoting angiogenesis and accelerating the process of bone defect repair.…”
Section: Bp-based Composite Biomaterials For Tissue Repairmentioning
confidence: 99%
“…In vivo studies from a model of a skull lesion in a rabbit shown that BPNs accelerated bone repair. Xu et al [ 37 ] prepared scaffolds by loading BPNs and deferoxamine (BPN-DFO) into gelatin hydrogels using a similar approach. In ischemic tibial areas of SD (Sprague Dawley) rats with acute femoral artery blockage, the scaffolds displayed excellent swelling, degradation, and release rates, and significantly enhanced osteogenesis and blood vessel development.…”
Section: Biomedical Application Of Black Phosphorus Hybrids Hydrogelmentioning
confidence: 99%
“…In contrast, in situ hydrogels fabricated with calcium-enriched nano-fibrillated cellulose exhibited improved biocompatibility, cell attachment, alkaline phosphatase, and calcium deposition activity [62]. Hydroxyapatite, being one of the most biocompatible agents, combined with cellulose to develop into nanocomposites for bone cell proliferation, were three-dimensionally printed and evaluated for the sustained release of strontium and calcium ions and substantial proliferation, bone marrow stem cell differentiation, and bone tissue revival [63]. In another study, cellulose nanocrystals doped with gelatin and alginate developed into 3D-printed hydrogel scaffolds presented considerable matrix mineralization in the bone tissue [64].…”
Section: Cellulosementioning
confidence: 99%